Design of a novel tri-axis ZnO nanowires based piezoelectric accelerometer - Muhammad Sohaib Khan; Hassan Elahi; Muhammad Mubasher Saleem; Masood Ur Rehman; Muhammad Abdullah Tayyab; Mohsin Islam Tiwana (PLoS ONE, 2025)
Micro-Electromechanical Systems (MEMS) are pivotal in modern technology, serving as components like accelerometers, gyroscopes, and pressure sensors in various applications. MEMS accelerometers are key components used for measuring motion and vibrations in a wide range of systems. This paper presents the proposed design of a ZnO nanowires-based piezoelectric accelerometer. Owing to the ZnO nanowires’ unique piezoelectric properties, the accelerometer can measure acceleration in three axes. A mathematical model is derived to analyze the behavior of nanowires under applied acceleration. Finite Element Method (FEM) simulations were carried out to evaluate the performance of the accelerometer. The key parameters of the accelerometer such as mechanical deformation, stress, voltage, and sensitivity are evaluated while applying a dynamic acceleration of 0.1 g and static acceleration of up to 50 g. The simulation results show a sensitivity of 0.25 V/g for an applied acceleration in the x and y axes (in-plane acceleration) and 1.40 V/g sensitivity was achieved in the z-axis (out-of-plane acceleration). The acceleration analysis reveals that the range and sensitivity of the sensor are high, that it can measure acceleration in three axes, and it also shows a linear behavior under static acceleration. The proposed accelerometer’s tri-axis acceleration sensing and self-powered capability make it an excellent choice for integration in biomedical applications.